Portable and Non-Invasive System for Gas Exchange Dynamics Estimation and Energy Expenditure as an Indicator of Metabolic State - Realpe Alvarez, Gerardo; Jose Miguel; Esteban Emilio; Carlos Alejandro (Revista Mexicana de Ingenieria Biomedica, 2025)
Accurate estimation of energy expenditure and gas exchange dynamics is essential for health monitoring and performance optimization. This study addresses the limitations of traditional systems by developing a portable, non-invasive, and real-time solution that correlates physiological signals with energy metabolism. The proposed system estimates energy expenditure and metabolic state using oxygen and carbon dioxide flows derived from non-invasive variables such as respiratory ventilation and heart rate. It utilizes Bluetooth Low Energy (BLE) for wireless communication and includes user-friendly interfaces for smartphones and computers to facilitate data visualization and recording. Calibration is performed using a calorimeter, resulting in an average estimation error of 14.83%. The system demonstrates reliable performance under various conditions, providing real-time estimations of energy expenditure and gas exchange. Its portability and ergonomic design improve usability; however, precise calibration remains essential, and broader testing is required to validate robustness. A key advantage of the system is its ability to operate entirely offline, relying solely on BLE for data transmission, making it suitable for real-time monitoring in diverse environments.